PENGARUH MEDIA DIORAMA TERHADAP KETERAMPILAN MENULIS TEKS PROSEDUR SISWA KELAS IV SDN PAMULIHAN KECAMATAN PAMULIHAN KABUPATEN SUMEDANG TAHUN PELAJARAN 2024/2025 - Suci Adawiatul Karomah; Sutarman; Nia Royani (LPPM UNSAP & Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This research was motivated by the low writing skills of procedural texts of grade IV students of Pamulihan Elementary School, Pamulihan District, Sumedang Regency in the 2024/2025 Academic Year. Students' skills in writing procedural texts are still not optimal in terms of structure, namely; the suitability of the title to the content, the choice of diction so that the same words are repeated. This is because vocabulary and language mastery are still minimal and limited stimulation of imagination is caused by less varied learning, resulting in a lack of skills in stringing words together. The purpose of this study was to determine the effect of diorama media on procedural text writing skills. This type of research is quantitative research using the Pre-Experimental method with the One-Group Pretest-Posttest Design. The population taken was all 18 fourth-grade students of SDN Pamulihan with a saturated sampling technique. The data collection technique used in this study was a test technique. While the research instrument was in the form of pretest-posttest questions with a one-item descriptive type. The data analysis technique used was the Liliefors normality test and the paired t-test. Based on the results of data analysis and hypothesis testing that had been carried out, it was found that at the α = 5% level, thitung 41.534 ≥ ttabel 1.753 was obtained. So it can be stated that H0 is rejected and Ha is accepted, which means that diorama media has a significant effect on the writing skills of procedural texts of fourth-grade students of SDN Pamulihan, Pamulihan District, Sumedang Regency, 2024/2025 Academic Year.